2009
DOI: 10.1021/jf901693j
|View full text |Cite
|
Sign up to set email alerts
|

Aroma Development during Ripening ofFragaria chiloensisFruit and Participation of an Alcohol Acyltransferase (FcAAT1) Gene

Abstract: Fragaria chiloensis is characterized for having great aroma and flavor properties. Using headspace-SPME different volatile compounds were identified and quantified during development and ripening of the fruit. The headspace was dominated by esters, butyl acetate, ethyl acetate, ethyl butanoate and ethyl hexanoate being the most abundant in fully ripe fruit. As esters are important for aroma and synthesized through alcohol acyltransferases (AAT), a full-length cDNA (FcAAT1) was isolated from F. chiloensis fruit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 35 publications
0
46
0
Order By: Relevance
“…In this context, other poorly active or inactive acyltransferase homologs (e.g., AtCER2 and ZmGlossy2) containing glutamic acid instead of aspartic acid in DFGWG motif have been previously reported (Tacke et al 1995;Xia et al 1996). In addition, a third conserved motif, LSxTLxxxYxxxG (Aharoni et al 2000;El-Sharkawy et al 2005;Gonzalez et al 2009;Sharma et al 2013), which is less conserved among acyltransferase genes, is present in LiAAT-4 with a modification of threonine 73 to isoleucine 73 . Only leucine 74 , tyrosine 78 and glycine 82 are present in LiAAT-3 for the third motif.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, other poorly active or inactive acyltransferase homologs (e.g., AtCER2 and ZmGlossy2) containing glutamic acid instead of aspartic acid in DFGWG motif have been previously reported (Tacke et al 1995;Xia et al 1996). In addition, a third conserved motif, LSxTLxxxYxxxG (Aharoni et al 2000;El-Sharkawy et al 2005;Gonzalez et al 2009;Sharma et al 2013), which is less conserved among acyltransferase genes, is present in LiAAT-4 with a modification of threonine 73 to isoleucine 73 . Only leucine 74 , tyrosine 78 and glycine 82 are present in LiAAT-3 for the third motif.…”
Section: Discussionmentioning
confidence: 99%
“…AAT activity of recombinant VpAAT1 protein was quantified by its ability to convert alcohols and acyl-CoAs into the corresponding ester [24,25]. AAT activity was assayed in 500 L of total volume in the presence of 2 mM benzyl alcohol and 250 M acetyl-CoA in 50 mM Tris-HCl (pH 7.5) buffer containing 10% (v/v) glycerol and 1 mM dithiothreitol (DTT) [8,9].…”
Section: Assay Of Aat Activity and Kinetic Parametersmentioning
confidence: 99%
“…Only two reports have identified the profile of volatile compounds in F. chiloensis . The main compounds identified include esters, some alcohols and ketones . However, to our knowledge, there are no reports of gas chromatography–olfactometry (GC‐O) of volatile compounds in F. chiloensis .…”
Section: Introductionmentioning
confidence: 99%
“…The main compounds identified include esters, some alcohols and ketones. 3,21 However, to our knowledge, there are no reports of gas chromatography-olfactometry (GC-O) of volatile compounds in F. chiloensis. In this study, we tentatively identified the volatile compounds that might contribute to the aroma of fresh white strawberry fruits using three different extraction methods: solvent-assisted flavor evaporation technique (SAFE), headspace solid-phase microextraction (HS-SPME) and liquid-liquid extraction (LLE).…”
Section: Introductionmentioning
confidence: 99%